A review of the elements of nature and the Malay cultural landscape through Malay literature - Hussain, Mohd Amirul; Mohd Yunos, Mohd Yazid; Ismail, Nor Atiah; Mohd Ariffin, Noor Fazamimah; Ismail, Sumarni (MDPI, 2020)
Research on the Malay cultural landscape in the Malay Archipelago is based on several factors, which include function, tradition, and the Malay culture. These factors are widely found in Malay literature, which plays a significant role in designing the landscape of Malay culture. Malay literature includes Old Malay manuscripts, Hikayat Melayu (Malay folktales), and Malay poetry, all of which are based on the beliefs, mindsets, and culture of the Malay community. These are demonstrated in a tangible or intangible manner through the environment of the traditional Malay lifestyle, inherent in Malay life values and in the symbolism of places. This review employed a document analysis to identify the elements and components of the Malay cultural landscape and its metaphorical aspects, as reflected in the aforementioned four types of Malay literature. Moreover, this review obtained information on the elements of the Malay cultural landscape that determine and explain the nature, function, and similarity of these aspects through symbolism in the landscape and culture of the Malays in Malaysia. Indirectly, this review proved the long existence of a systematic Malay cultural landscape throughout the Malay Archipelago that remains essential for future cultural sustainability. Finally, elements of the Malay landscape were identified, which could be applied as guidelines for designers in outlining a Malay cultural landscape.